Menuju Masa Depan Yang Berkelanjutan : Mengoptimalkan Media Sosial Untuk Meningkatkan Kesadaran SDGs 2030 - Rafly Aufa Thoriq; Vani Rahma Sari; Ichsan Fauzi Rachman (Universitas Maritim AMNI Semarang, 2024)
Social media, as an important tool for disseminating information and mobilizing action, has become increasingly important in the current era of computers and the internet. This article explains how social media can be used optimally to increase public awareness about the 2030 Sustainable Development Goals (SDGs). SDGs is a global agenda that includes 17 goals in various fields such as social, economic and environmental. This article aims to provide in-depth insight into how social media can be a powerful tool for achieving the 2030 SDGs by investigating effective strategies and practices. The Global Sustainable Development Goals (SDGs) agenda includes 17 ambitious goals in areas such as social, economic and environmental. This article aims to provide in-depth insight into how social media can be a powerful tool for achieving the 2030 SDGs by exploring effective strategies and practices. By considering various aspects, such as target audience, type of content, and success measurement metrics, this article provides a comprehensive guide for practitioners and SDGs activists to maximize the potential of social media.